South Asian perspectives on development. - South Asian Students Alliance:::Creator::::::::::::; Asian Pacific Council; Dean of Student Life; Multicultural Action Team;:::Contributor::::::::::::
Leaflet contains promotion for and description of the second semi-annual conference on the socio-economic development in South Asian subcontinent within the context of global capitalism. The conference will highlight the issues of ecology, gender, culture, global trends, and alternative models of modernization. The conference was held in Morgan hall at UC Berkeley.